KEKUATAN HUKUM PELIMPAHAN WEWENANG DARI DOKTER KEPADA NERS DITINJAU DARI ASPEK PIDANA DAN PERDATA - Aning Pattypeilohy; Sutarno Sutarno; Adriano Adriano (Legality : Jurnal Ilmiah Hukum, 2017)
This study aims to provide an overview of the power of law in the delegation of authority from the doctor to ners both in writing and not written. In performing health services, especially in performing medical acts, it is necessary to transfer the authority of medical personnel to health personnel in order to create a comprehensive and quality health service, this has been regulated in related legislation. Ners is a profession professional and independent, in carrying out its professional duties ners work in accordance with service standards, standard operating procedures and the provisions of the Act-legislation. As a health worker, the ners may receive a delegation of authority only in writing from the doctor to him or her so that the delegate has the force of law. With the delegation of authority in health services, if there is a loss or legal problems in the future, doctors as authors and recipients of authority can be held accountable both criminal and civil.